Alone in the Academic Ultraperiphery: Online Doctoral Candidates’ Quest to Belong, Thrive, and Succeed - Melián, Efrem; Meneses, Julio (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2024)
Despite the increasing number of non-traditional doctoral researchers, this population’s experiences remain largely understudied and their voices unheard. Through in-depth interviews with 24 part-time online doctoral candidates, we explored the perceived facilitators and barriers to academic integration and sense of belonging, as well as how online delivery influences the doctoral journey. Reflexive thematic analysis revealed a strong drive for participation, sometimes matched by the supervisor but rarely supported by the institution, which in the end does not sufficiently promote community building. Online delivery was viewed as both a blessing for the accessibility it enabled and a curse due to pervasive feelings of isolation and virtually non-existent peer networks. Online doctoral researchers coped by breaking free from the fully online model whenever possible to seek in-person and synchronous interactions and guidance. We conclude that online doctoral candidates constitute an ultraperipheral population in the academic landscape. Support provided by online PhD programmes should be modelled after the actual needs of their non-traditional students.